Cost of Magnetic Resonance Imaging (MRI) in a Specialized Cancer Hospital - Boonkerd, Arkorn; Chunpenmongkol, Sranut; Uadrang, Surin (Journal of The Department of Medical Services, 2022)
Background: Cancer is an importance global health problem. Radiographic imaging, like magnetic resonance imaging (MRI) help to improved diagnosis, prognosis, and treatment planning for cancer. However, previous studies have never been reported on the unit cost and the break-even point of MRI in the cancer patients. Objective: This study aimed to analyzing the unit cost and break-even point of MRI. Method: The data were retrieved from the medical records between January 1st, 2017 and December 31st, 2017 at Lopburi Cancer Hospital. Results: The study was found that there were totally 493 services. The average capital cost was 7,463,083.00 baht, the average material cost was 3,624,610.42 baht and the average labor cost was 547,777.27 baht. The unit cost was 28,321.63 baht/ service and the average break-even point was 1,948 service/ year. That was not full workload and effect to the highly unit cost. Conclusion: MRI services for cancer hospital represents a highly cost. The cause is small amount of patient, so that the hospital should be co-operate with the hospital in the health network area to increasing the MRI service for the generally and sustainability service.